PENGARUH TOTAL ASSET TURNOVER (TATO), CURRENT RATIO (CR), DAN DEBT TO EQUITY RASIO (DER) TERHADAP RETURN ON ASSET (ROA): Studi Kasus Pada Perusahaan Logam dan Mineral lainnya yang Terdaftar di Bursa Efek Indonesia Periode 2020-2023 - Fathor, Khresna Adityo; Saputra, Fendi (Gapenas Publisher, 2024)
This research is motivated by the Return on Asset (ROA) level in metal and other mineral companies which had increased after the Covid-19 period but decreased in the following year. Based on several financial literature books and previous research, the financial ratios Total Asset Turnover (TATO), Current Ratio (CR), and Debt to Equity Ratio (DER) are used in this study to assess the ROA level. The methodology of this research uses panel data with 8 samples of companies that consistently report their finances and are classified as metal and other mineral companies on the IDX in the 2020-2023 period. The results of the study show that TATO has a significant positive effect on ROA, while CR does not show a significant effect, and DER has a negative and significant effect on ROA